Synaptic defects in a drosophila model of muscular dystrophy - Sidisky, Jessica M.; Winters, Alex; Caratenuto, Russell; Babcock, Daniel T. (Frontiers in Cellular Neuroscience, 2024)
Muscular dystrophies are a devastating class of diseases that result in a progressive loss of muscle integrity. Duchenne Muscular Dystrophy, the most prevalent form of Muscular Dystrophy, is due to the loss of functional Dystrophin. While much is known regarding destruction of muscle tissue in these diseases, much less is known regarding the synaptic defects that also occur in these diseases. Synaptic defects are also among the earliest hallmarks of neurodegenerative diseases, including the neuromuscular disease Amyotrophic Lateral Sclerosis (ALS). Our current study investigates synaptic defects within adult muscle tissues as well as presynaptic motor neurons in Drosophila dystrophin mutants. Here we demonstrate that the progressive, age-dependent loss of flight ability in dystrophin mutants is accompanied by disorganization of Neuromuscular Junctions (NMJs), including impaired localization of both presynaptic and postsynaptic markers. We show that these synaptic defects, including presynaptic defects within motor neurons, are due to the loss of Dystrophin specifically within muscles. These results should help to better understand the early synaptic defects preceding cell loss in neuromuscular disorders.